Optimizing Ecotourism Management of Tajungkima Hamlet: A Study of Social Entrepreneurship and Islamic Sustainability - Khoiri, Ahmad; Rufaedah, Dina Anisya; Irfanah, Ru'yatul; Aeni, Desy Salma; Hasan, Khalid Ibrahim Alu (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2023)
Ecotourism in Tajungkima Hamlet serves as a form of social entrepreneurship activity where the Tourism Awareness Group (Pokdarwis) and the local community jointly manage this freehold land to enhance the economy and promote shared prosperity. This research aims to provide a description and analysis of the optimization of Pokdarwis' role in ecotourism management with a social entrepreneurship approach, while also examining sustainability from an Islamic perspective. The study utilizes qualitative research methods with a descriptive system. Data collection techniques involve observation, interviews, and documentation. Data analysis includes reduction, presentation, and drawing conclusions. The findings reveal that the process of social entrepreneurship in the development of Somor-Somor Beach and Tanjung Ga'ang ecotourism contributes to a comprehensive understanding of Pokdarwis' role in ecotourism management through a social entrepreneurship approach. Additionally, it emphasizes the significance of integrating sustainability principles from an Islamic standpoint. The research emphasizes the importance of holistic and responsible practices that enhance societal socio-economic well-being while addressing environmental concerns. These insights can guide policymakers, local communities, and stakeholders in developing and promoting sustainable Ecotourism initiatives rooted in Islamic values.